2020
DOI: 10.1039/d0ra05990k
|View full text |Cite
|
Sign up to set email alerts
|

Highly transparent and flexible Ag nanowire-embedded silk fibroin electrodes for biocompatible flexible and transparent heater

Abstract: We demonstrated the characteristics of a transparent, flexible silver nanowire-embedded silk fibroin substrate that can be used as a flexible and biocompatible electrode for wearable electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Park et al examined the attributes of AgNW integrated SF substrate, which can be utilized to develop transparent and flexible heaters (TFHs) and also to construct high-performance electrodes. 68 The substrate exhibited a little sheet resistance of only 15 Ω sq −1 , 85.1% optical transmittance, and 1 mm critical bending radius. Most importantly, it showed intriguing results while undergoing fatigue bending, folding and rolling tests in which its surface resistance was unchanged without any surface crack.…”
Section: Silk/nanomaterials Interfaces For Wearable and Bioelectronic...mentioning
confidence: 99%
See 2 more Smart Citations
“…Park et al examined the attributes of AgNW integrated SF substrate, which can be utilized to develop transparent and flexible heaters (TFHs) and also to construct high-performance electrodes. 68 The substrate exhibited a little sheet resistance of only 15 Ω sq −1 , 85.1% optical transmittance, and 1 mm critical bending radius. Most importantly, it showed intriguing results while undergoing fatigue bending, folding and rolling tests in which its surface resistance was unchanged without any surface crack.…”
Section: Silk/nanomaterials Interfaces For Wearable and Bioelectronic...mentioning
confidence: 99%
“…67 Another study observed higher optical transmittance for silk fibroin/ AgNW film at a short wavelength below 375 nm. 68 The gold film deposited onto the silk also improves its optical properties. The larger optical transparency value of over 60% was attained at 450−850 nm with a gold film thickness of 3 nm.…”
Section: Overview Chemical Structure and Morphology Of Silkmentioning
confidence: 99%
See 1 more Smart Citation
“…A flexible and transparent conductive electrode (FTCE) is a thin film with high transparency, high conductivity, and outstanding flexibility [1][2][3]. Due to the rapid advancements in flexible electronics and wearable devices, FTCEs have gained a great deal of attention as a key component of flexible displays [4][5][6], flexible touch panels [7][8][9], flexible thin film heaters (TFHs) [10][11][12][13][14][15][16], photoelectric devices [17][18][19][20], and wearable electronics [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…A flexible and transparent conductive electrode (FTCE) is a thin film with high transparency, high conductivity, and outstanding flexibility [ 1–3 ]. Due to the rapid advancements in flexible electronics and wearable devices, FTCEs have gained a great deal of attention as a key component of flexible displays [ 4–6 ], flexible touch panels [ 7–9 ], flexible thin film heaters (TFHs) [ 10–16 ], photoelectric devices [ 17–20 ], and wearable electronics [ 21–23 ]. Currently, most flexible electronics and wearable devices use Sn-doped In 2 O 3 (ITO) film coated on a flexible substrate through a typical magnetron sputtering process [ 24–26 ] owing to the high conductivity and transparency of commercially available ITO films.…”
Section: Introductionmentioning
confidence: 99%